Peningkatan Hasil Belajar PAK Dengan Model Problem Based Learning Materi Terlibat Dalam Hidup Menggereja Fase C Kelas V SD Santo Antonius Bangun Mulia Medan - Risma Br Ginting; Hartutik Hartutik; Paulus Asnadi (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The results of observations regarding student creativity in teaching and learning activities at Santo Antonius Bangun Mulia Elementary School, Medan, especially in the subjects of Catholic Religious Education and Character, are very lacking, as well as learning outcomes that have not reached the predetermined target, only % complete KKM. The aim of this research is to improve creative and cognitive aspects by applying the Problem Based Learning learning method phase C for class 5 at Santo Antonius Bangun Mulia Elementary School, Medan. This Classroom Action Research (PTK) consists of 4 stages, namely, planning, implementation, evaluation and reflection. The research subjects were 25 Class 5 A Face C students. Obtaining data by: 1) observation with observation indicators Pancasila Student Profile dimensions of faith and devotion to God Almighty and having noble character (P3): Understanding the main elements of religious beliefs, Recognizing the role of religious beliefs in life, Understanding religious moral teachings, Implementing worship regularly, pray independently, celebrate religious holidays, understand the meaning of the holidays and 2) test material learning results with achievement targets: Proficient 35%, Proficient 55%, Adequate 10%, only 0% developed. The research results showed: There was an increase in the creative aspect of P3 from cycle 1 to 2 by 5.7%. In terms of the learning achievement aspect, there was an increase in the number of achievement targets from proficient 32% to 56%, proficient 36% to 24% decent 32% to 20%. Suggestion: in the process of teaching and learning activities, teachers should apply a variety of learning methods and plan one dimension of the Pancasila Student Profile.